Influência transgeracional do enriquecimento ambiental nos aspectos fenotípicos e epigenéticos em fêmeas de Mus musculus da linhagem LG/J - Machado Junior, Edgar de Lima (2022)
Currently, widely used in zoos and aquariums, in addition to being adopted in vivariums, environmental enrichment aims to allow the captive animal to express its species-specific behavior, improving its quality of life. Maternal care is intrinsic to emotionality, as a female to satisfactorily care for her offspring needs to be in excellent physical and emotional condition. When we think about mammals, it is known that maternal care has complex genetic bases and is susceptible to interference from environmental factors. Result of the individual-environment interaction, epigenetics comprises molecular changes in DNA and histone proteins, which are likely to be inherited, do not modify the DNA sequence and may undergo reversibility. This study aimed to verify the influence of environmental enrichment in a transgenerational way in females of Mus musculus LG/J on aspects of emotionality and maternal care. The females studied were divided into four groups and had never been exposed to environmental enrichment, namely: female daughters of mothers who were exposed to environmental enrichment from the pubertal to maternal stage, female daughters of mothers who were never exposed to environmental enrichment, female daughters from mothers who were submitted to environmental enrichment in the maternal phase and females daughters of mothers who were exposed to environmental enrichment only in the maternal phase. Emotionality was analyzed using open field, elevated plus maze and forced swimming tests. Maternal care was analyzed by the mother's postures in building a nest, performing placentophagy, offering milk to the young, having aggressive behavior against intruders and maintaining the size of the born litter. The results showed that phenotypically, the influences of environmental enrichment on emotionality and maternal care were not inherited, with females from non-enriched mothers having greater reproductive success and a lower rate of anxiety. The study showed that in this case, environmental enrichment must be applied continuously, so if a generation has been enriched, the offspring cannot be deprived of such a mechanism that aims to improve animal welfare.